An Introduction to Mushroom (IntechOpen, 2021)
The mushroom has a wide number of medicinal properties such as being an antioxidant, antimicrobial, anticancer, antidiabetic, immune enhancer, and also used for the treatment of various diseases such as anthelmintic, anti-inflammatory, antipyretics, etc. According to current information, there are approximately twelve-thousand species in the world, and out of them, 2000 species are reported as being edible. Around 35 edible mushroom varieties are cultivated commercially, whereas almost 200 wild species could be used for medicinal purposes. This book also covers the diversity of edible mushrooms and describes several applications as an alternative source for food production and clinical approach. This book includes: • the diverse types of mushroom and their enzymatic activity • importance of nutritional properties along with their food product development • industrial and clinical applications of macro fungi, i.e., degradation of dyes, anticancer, antimicrobial, antioxidant, etc.